2020
DOI: 10.1101/2020.08.20.260117
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expression partitioning of duplicate genes at single cell resolution inArabidopsisroots

Abstract: Gene duplication is a key evolutionary phenomenon, prevalent in all organisms but particularly so in plants, where whole genome duplication (WGD; polyploidy) is a major force in genome evolution. Much effort has been expended in attempting to understand the evolution of duplicate genes, addressing such questions as why some paralogue pairs rapidly return to single copy status whereas, in other pairs, paralogues are retained and may (or may not) diverge in expression pattern or function. The effect of a gene - … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 115 publications
(172 reference statements)
0
1
0
Order By: Relevance
“…3). Indeed, a recent study leveraging Arabidopsis single-cell data found extreme cell typespecific expression bias among pairs of homologous genes (gene duplicates) 50 . Using this information could result in substantial improvements to plant functional gene annotations across species.…”
Section: Grand Research Challenges For Single-cell Profiling Of Plantsmentioning
confidence: 99%
“…3). Indeed, a recent study leveraging Arabidopsis single-cell data found extreme cell typespecific expression bias among pairs of homologous genes (gene duplicates) 50 . Using this information could result in substantial improvements to plant functional gene annotations across species.…”
Section: Grand Research Challenges For Single-cell Profiling Of Plantsmentioning
confidence: 99%